Réponses

Meilleure réponse !
2014-02-04T23:59:03+01:00
Bonsoir

1) -3x - 13 = 8x - 5
-3x - 8x = -5 + 13
-11x = 8
x = -8/11

3 * (-1 - 2t) = 4 * (1 - 5t)
-3 - 6t = 4 - 20t
-6t + 20t = 4 + 3
-14t = 7
t = 7/(-14)
t = -1/2
Merciiiiiiiii!!
As-tu les vérifications, s'il te plait? ://
Attention au 2ème !
Il faut lire :
14t = 7
t = 7/14
t = 1/2
Vérification :
-3*(-8/11) -13 = 8*(-8/11) - 5
24/11 - 143/11 = -64/11 - 55/11
-119/11 = -119/11

3*[-1 - 2*(1/2)] = 4*[1 - 5*(1/2)]
3*(-1 - 1)=4*(2/2 - 5/2)
3*(-2) = 4*(-3/2)
-6 = -6